2020
DOI: 10.1136/annrheumdis-2020-eular.5440
|View full text |Cite
|
Sign up to set email alerts
|

Ab0889 sarcopenia and Hip Fracture in Geriatric Population

Abstract: Background:Sarcopenia is a loss of skeletal muscle mass, muscle strength, and function, with an impact on the quality of life, increased risk of bone loss and fracture, which is associated with normal aging.Objectives:To determine the effect of sarcopenia on the recovery of patients after hip fracture, their fitness, functionality, and quality of lifeMethods:A prospective study had 60 patients with hip fractures of both sexes,> 65 years of age (70.8), in the experimental group of patients with sarcopenia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Fourteen studies were excluded for the following reasons: use of inappropriate sarcopenia diagnostic method (n = 7), lack of the minimum age requirements in the methodology (n = 5), duplicate publication (n = 1), and assessment of only the association between handgrip strength and functional prognosis instead of sarcopenia and its respective outcomes (n = 1). Thus, 10 studies and one scientific abstract were subjected to meta-analysis: nine prospective observational studies (Boskovic et al, 2020;González-Montalvo et al, 2016;Ho et al, 2016;Lang et al, 2018;Lim et al, 2018Lim et al, , 2020Malafarina et al, 2019;Steihaug et al, 2018), one cross-sectional study (Hida et al, 2013), and one retrospective study (Yoo et al, 2018; Figure 1). No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies were excluded for the following reasons: use of inappropriate sarcopenia diagnostic method (n = 7), lack of the minimum age requirements in the methodology (n = 5), duplicate publication (n = 1), and assessment of only the association between handgrip strength and functional prognosis instead of sarcopenia and its respective outcomes (n = 1). Thus, 10 studies and one scientific abstract were subjected to meta-analysis: nine prospective observational studies (Boskovic et al, 2020;González-Montalvo et al, 2016;Ho et al, 2016;Lang et al, 2018;Lim et al, 2018Lim et al, , 2020Malafarina et al, 2019;Steihaug et al, 2018), one cross-sectional study (Hida et al, 2013), and one retrospective study (Yoo et al, 2018; Figure 1). No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…An observational study conducted by Chen et al demonstrated that patients with a hip fracture and sarcopenia had significantly poorer BI scores and Euro Qol-5D scores (for assessing quality of life) than patients without sarcopenia before a hip fracture and at 6 months after surgery (Y. P. . Similarly, Boskovic et al noted a significant difference in all domains of quality of life between older adults with hip fractures and sarcopenia and the control group by using Sarcopenia and Quality of Life (SarQol) questionnaires (p < .005; Boskovic et al, 2020). A prospective study included 181 consecutive patients with femoral neck fracture with 6 months of follow-up, using Harris hip scores for functional evaluation (odds ratio: 2.887, p = .008; Lang et al, 2018).…”
Section: Postoperative Functional Recoverymentioning
confidence: 91%
See 1 more Smart Citation